Creating security zones around the land of historical and cultural significanse - Peresolyak, V. Yu.; Savchak, V. V. (Land Management, Cadastre and Land Monitoring, 2017)
Problems features on establishment of protection zones around the lands of historical and cultural significance are overlooked in this article. An order of development pro‐ jects on land management restrictions and encumbrance’s protection zones around the lands of historical and cultural significance is offered, followed by their inclusion in the database of the State Land Cadastre (SLC). State cadastre of historical ‐ cultural lands of Ukraine must be formed on the basis of Land Cadastre. It will allow to form the legal, socio ‐ economic factors for Land Management in security zones of histori‐ cal and cultural significance by local governments and state bodies